89.3k views
4 votes
I NEED HELP PLEASE ASAP !

I NEED HELP PLEASE ASAP !-example-1
User Bhargavi
by
5.2k points

2 Answers

6 votes

Answer:

- 6

Explanation:

(x²⁵)⁻⁶/(x⁻³)⁴⁸ =

= (x²⁵ˣ⁻⁶)/(x⁻³ˣ⁴⁸)

= (x ⁻¹⁵⁰)/(x ⁻¹⁴⁴)

= x ⁻¹⁵⁰ ⁻⁽⁻¹⁴⁴⁾

= x ⁻¹⁵⁰⁺¹⁴⁴

= x ⁻⁶

User Rob Paterson
by
5.1k points
1 vote

The first rule you need to know is


(a^b)^c=a^(bc)

So, you have


((x^(25))^(-6))/((x^(-3))^(48))=(x^(25\cdot(-6)))/(x^(-3\cdot 48))=(x^(-150))/(x^(-144))

The second rule you need to know is


(a^b)/(a^c)=a^(b-c)

So, you have


(x^(-150))/(x^(-144))=x^(-150-(-144))=x^(-150+144)=x^(-6)

User Roger Heathcote
by
4.6k points